Impact of recent drug use on the efficacy of elbasvir/grazoprevir for HCV‐infected people on opioid agonist therapy. Issue 6 (15th April 2021) - Macías, Juan; Téllez, Francisco; de los Santos, Ignacio; Morano, Luis E.; Merino, Dolores; Granados, Rafael; Vera‐Mendez, Francisco; González‐Serna, Alejandro; Campo‐Moneo, Esther; García‐Fraile, Lucio; García, Federico; Real, Luis M.; et al.
Abstract: Elbasvir/grazoprevir (EBR/GZR) use in drug users on opiate agonist therapy (OAT) is supported by the C‐EDGE Co‐STAR trial. SVR rates in this study were within those found in the rest of patients included by the EBR/GZR development programme. In clinical practice, however, efficacy could theoretically be lower. Thus, we aimed at evaluating the SVR rates of EBR/GZR among people who injected drugs (PWID) with and without OAT in clinical practice. Patients starting EBR/GZR included in the HEPAVIR‐DAA (NCT02057003), recruiting HIV/HCV‐coinfected patients or the GEHEP‐MONO (NCT02333292), including HCV‐monoinfected individuals, prospective cohorts were analysed. Overall SVR12 (ITT), discontinuations due to adverse effects and drop‐outs were evaluated. The same analysis was carried out for PWID with and without OAT. 336 patients had started EBR/GZR and reached the SVR12 evaluation date. 318 [95%, 95% confidence interval (95% CI): 92%‐98%] patients achieved SVR12. SVR12 was 97% (95% CI: 93%‐99%, n/N = 141/145) among people who never used injecting drugs, 94% (95% CI: 88%‐97%, n/N = 117/125) among PWIDs without OAT and 91% (95% CI: 81%‐97%, n/N = 60/66) among PWIDs with OAT ( p = 0.134). Five (1.5%) patients showed relapses, and two (0.6%) individuals showed viral breakthrough. The SVR12 rate for recent drug users was 69% ( n/N = 18/26) compared with 97% ( n/N = 276/284) for individuals without recent drug use (in the prior year) ( p < 0.001). Among recent drug users, three (12%) showed relapses, and five (19%) were lost‐to‐follow‐up. The SVR rates achieved with EBR/GZR were high in real‐world conditions of use. However, PWID with recent drug use reach suboptimal response rates with EBR/GZR.